THE EFFECT OF TIME BUDGET PRESSURE AND DYSFUNCTIONAL AUDITOR BEHAVIOR ON AUDIT QUALITY: A CASE STUDY IN AN AUDIT FIRM IN INDONESIA - Gemintia Padma Asriningpuri; Frank Gruben (Diponegoro Journal of Accounting, 2021)
Purpose The aim of this research is to examine the effect of dysfunctional auditor behaviour on audit quality under time budget pressure. This research also investigates the relationship between dysfunctional auditor behaviour and time budget pressure.Design/ methodology/approach This research was conducted by doing structured interviews with 4 auditors at Chris Hermawan Public Accountant Firm, which located in Bandung, Indonesia.Findings The results explain that time budget pressure has impacts on dysfunctional audit behaviour, such as premature sign-offs, the lack of audit procedure, and gathering insufficient evidence. Pressure (time budget) is the condition that has both positive and negative effects on individual behaviour. Pressure may cause people to act dysfunctionally or motivate them to give their best even though their work requires a lot of energy and effort to solve problems. However, if the individual suffers any excessive pressure, it will decrease their job performance, such as dysfunctional behaviours. These results also indicate that dysfunctional audit behaviour has an adverse effect on audit quality. The increase in dysfunctional behaviour will reduce the auditor's ability to identify material misstatement in the financial statement. Therefore, dysfunctional audit behaviour can reduce audit quality that has an impact on the auditing profession. This research also offered recommendations for the audit firm to reduce the time budget pressure, dysfunctional auditor behavior, and poor audit quality.